Rancang Bangun Layanan Private cloud Berbasis Infrastructure as a Service Menggunakan OpenStack dengan Metode Network Development Life Cycle(NDLC) - Kamdan; Somantri; Muhamad Galih Sundayana; Ivana Lucia Kharisma (STMIK Budi Darma, 2023)
This study aims to implement the design of an IaaS-based private cloud service using the OpenStack platform at SMA Negeri 1 Warungkiara. The data collection method used is qualitative, allowing researchers to gain in-depth understanding of issues related to IT infrastructure management in schools, particularly concerning file storage and network security. The research results demonstrate that adopting private cloud services effectively addresses these issues and provides significant benefits in IT infrastructure management. Previously, SMA Negeri 1 Warungkiara used conventional methods for file storage, which had limitations in storage capacity and data security. However, by using IaaS-based private cloud services, the storage capacity at SMA Negeri 1 Warungkiara can be significantly increased, and data security and network performance are improved. The contribution of this research lies in developing IaaS-based private cloud services that suit the needs of SMA Negeri 1 Warungkiara and providing practical guidance in the implementation and management of these services. Practical recommendations resulting from this research include involving all relevant parties in the implementation process, improving communication between involved parties, and ensuring user engagement in utilizing private cloud services. Furthermore, the development of theories in technical, management, and security aspects is also suggested to support further advancements in private cloud services. Subsequent research can involve evaluating performance and user satisfaction in implementing private cloud services in educational settings, by adding examples of webserver and dafodik implementations